Broadband Achromatic Transmission–Reflection‐Integrated Metasurface Based on Frequency Multiplexing and Dispersion Engineering. Issue 7 (20th January 2021) - Zhang, Zuojun; Wang, Jiangyu; Pu, Mingbo; Ma, Xiaoliang; Huang, Cheng; Guo, Yinghui; Luo, Xiangang
Abstract: Transmission–reflection‐integrated metasurfaces (TRIMs) provide an effective avenue to realize functionality integration and miniaturization of imaging and communication systems. However, most of the previous works suffer from large chromatic aberrations due to the intrinsic dispersive properties of the resonators constituting metasurfaces, which results in the meta‐devices working in a small operation bandwidth. Here, a broadband achromatic TRIM is proposed based on the frequency‐multiplexing scheme and dispersion engineering in transmission and reflection mode, respectively. As a proof of the scheme, 1D achromatic transmission–reflection‐integrated focusing metasurface and common‐caliber transmitarray and reflectarray flat plate antenna are demonstrated over a broad frequency range. The achromatic focusing in transmission mode and reflection mode with simulated focusing efficiencies of 13.12–17.21% and 14.57–20.86% are simultaneously realized at 12–18 and 19–24 GHz, respectively. The radiation gains increase by an average of 17.53 and 23.57 dB for the transmission mode and reflection mode relative to the bare standard rectangle waveguides. The scheme for achromatic and independent electromagnetic manipulation in transmission and reflection mode can also be applied to other frequency ranges and promise unprecedented progress for optical imaging and wireless telecommunication. Abstract : An achromatic metasurface integrating non‐interfering resonant phase reflectarray and geometrical phase transmitarray is proposed, which can simultaneously achieve broadband achromatism in transmission and reflection mode based on frequency‐multiplexing scheme and dispersion engineering. 1D achromatic transmission–reflection‐integrated focusing metasurface and common‐caliber transmitarray/reflectarray flat plate antenna are demonstrated over a broad frequency range.